Thessaloniki and the Thessaloniki International Trade Fair. A Case of Conflict? - Christos Th. Kousidonis (European Regional Science Association (ERSA), 2006)
The plans of the 'Thessaloniki International Trade Fair (TIF) SA' to develop the area occupied by the facilities of the Trade Fair ignited a strong debate. The TIF SA was established in 1925 and the General Trade Fair, as it came to be called, organised on an annual basis, has since become a major event for the city of Thessaloniki and its region. The activities of the TIF SA expanded in a wide range of related activities. On the other hand, the General Trade Fair is currently facing very serious competition. The General Trade Fair takes place in facilities located in an 18-ha property of which TIF SA is the sole proprietor. This property, roughly located at the geometric centre of the city, is part of a wider, ribbon-like, zone extending from the sea front to the grove surrounding the city, comprised of public open spaces and low ratio of floor-space-to-plot areas, occupied by educational, cultural, recreational, sports and exhibition activities of at least city scale importance, and owned by the public sector. Proposals for relocating the General Trade Fair first appeared in 1985. For as long as Thessaloniki was a candidate for the 2008 EXPO, the TIF SA was seriously considering relocating the Trade Fair to one of its properties outside Thessaloniki. Last fall, the TIF SA announced preliminary plans for renovating the facilities in the centre and, in the process, intensifying the use of its property mainly with a hotel, movie theatres and new retail facilities. On the other side, major actors, including the Mayor, clearly oppose to these plans. The conflict generates debate and scenarios revolving around two apparent extremes: Adoption of the TIF SA proposal or redevelopment of the wider, ribbon-like, zone with priority given to the public open spaces and the pedestrian. If Thessaloniki or the TIF SA were to eventually prepare a dossier for the 2015 EXPO, the situation might call for drastic proposals encompassing new plans for the city and its region, economies of scale and concentration regarding the exhibition-related activities, and the make-up of the image of the city.
Keywords: 330